Anesthetic management of laparoscopic pyeloplasty in a Klippel-Feil syndrome patient with aortic coarctation: A multidisciplinary approach - Saxena, Ruchi; Gautam, Archana; Srivastava, Kuldeep (Indian Journal of Case Reports, 2025)
Klippel-Feil syndrome (KFS) is a rare congenital condition characterized by fusion of cervical vertebrae, often associated with other systemic anomalies, such as cardiac malformations and renal abnormalities. These patients pose significant anesthetic challenges due to difficult airway anatomy, potential cervical spine instability, and associated comorbidities. Beyond airway difficulty, KFS patients often have systemic issues further compounded by physiologic changes from laparoscopy, requiring tailored anesthetic planning. We present here anesthetic management of laparoscopic pyeloplasty for a solitary functioning kidney with pelvic-ureteric junction obstruction in a patient with recently diagnosed KFS with aortic coarctation. This case highlights the critical importance of thorough pre-operative assessment, meticulous planning, and a multidisciplinary team approach. Early identification of hidden abnormalities, preparedness for airway challenges, and collaborative perioperative care are vital to ensure safe outcomes in patients with complex syndromic presentations, such as KFS.